The Traditional Dance Inheritance System of the Saibatin Indigenous People in Keratuan Darah Putih as a Source of Cultural Literacy - Daryanti, Fitri; Sinaga Margaretha, Risma; Hani Saputri, Amelia (Mudra : jurnal seni budaya, 2025)
The inheritance of traditional dance within the Saibatin Traditional Lampung Community in Keratuan Darah Putih presents a significant challenge for the younger generation, as traditional dance is primarily performed during traditional marriage ceremonies. The central issue addressed in this article is the restricted inheritance system of traditional dances, which limits access to the younger generation. This research aims to analyze the inheritance system employed by the Saibatin indigenous people in the White Blood Region and their efforts to preserve traditional values amid a rapidly changing cultural landscape. Furthermore, this study explores how the values and meanings embedded in traditional dance serve as a source of cultural literacy for the Lampung community. This research adopts a qualitative approach with an ethnographic methodology. Data was collected through observation, in-depth interviews with traditional figures, dancers, and musicians, as well as field notes and documentation. Source triangulation was employed to ensure the credibility of the data. The data analysis followed the Miles and Huberman framework, which involved data collection, reduction, presentation, and conclusion. The findings indicate that the traditional dance inheritance system practiced by the Saibatin Indigenous people in Keratuan Darah Putih is primarily based on a vertical inheritance model grounded in the kinship system. This process occurs through the immediate family and the extended kinship network, supplemented by non-formal learning at the Intan studio.